Making Music in the Primary School : Whole Class Instrumental and Vocal Teaching. - Beach, Nick (Taylor & Francis, 2010)
An essential guide for teaching and learning music with the whole class.¨It provides a framework for successful musical experiences with large groups of children and is illustrated throughout with carefully designed activities to try out in the classroom. The guidance in this book will help you support and develop children's musical experience.